2015
DOI: 10.1093/gerona/glv181
|View full text |Cite
|
Sign up to set email alerts
|

Association Rules Analysis of Comorbidity and Multimorbidity: The Concord Health and Aging in Men Project

Abstract: Old age is characterized by a complex pattern of multimorbidity and comorbidity. Single disease definitions do not account for the prevalence and complexity of multimorbidity in older people and a new lexicon may be needed to underpin research and health care interventions for older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 30 publications
0
81
0
5
Order By: Relevance
“…Widely accepted equations were not developed with these considerations, thus necessitating the examination of predictive equation accuracy. Given that approximately half of patients admitted to the ICU are greater than 65 years of age and the majority of older adults have MCCs [4, 5], these patients are at increased risk of mortality and functional limitations.…”
Section: Age-related Conditions That Affect Reementioning
confidence: 99%
See 1 more Smart Citation
“…Widely accepted equations were not developed with these considerations, thus necessitating the examination of predictive equation accuracy. Given that approximately half of patients admitted to the ICU are greater than 65 years of age and the majority of older adults have MCCs [4, 5], these patients are at increased risk of mortality and functional limitations.…”
Section: Age-related Conditions That Affect Reementioning
confidence: 99%
“…Older patients have higher health care utilization, in addition to a greater chance of hospitalization compared to younger adults due to greater number of comorbidities, less physiologic reserve and lower premorbid functioning [2, 3]. Furthermore, the majority of older adults have at least one chronic condition [4, 5], which may lead to greater susceptibility of hospital-acquired infections and other complications that further contributes to decline in function [6]. Malnutrition is also a prevalent issue within the health care setting that can contribute to functional decline [7], yet estimates suggest only half of malnourished patients are recognized and treated [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…В зарубежных исследо-ваниях 1-4 сопутствующих заболевания выявляли у 70-75% пожилых [15][16][17], в РФ у больных пожилого воз-раста, госпитализированных в гастроэнтерологиче-ские отделения, одновременно диагностировали 5-8 нозологических форм [18]. В целенаправленном по-пуляционном исследовании, проанализировавшем 17 заболеваний, был продемонстрирован сложный пат-терн мультиморбидности и коморбидности в пожилом возрасте, который авторы подразделили на несколько кластеров (сосудистый, метаболический, нейродеге-неративный, ментальный в сочетании с другим кла-стером, и мышечноскелетный в сочетании с другим кла-стером) [17].…”
Section: коморбидностьunclassified
“…В зарубежных исследо-ваниях 1-4 сопутствующих заболевания выявляли у 70-75% пожилых [15][16][17], в РФ у больных пожилого воз-раста, госпитализированных в гастроэнтерологиче-ские отделения, одновременно диагностировали 5-8 нозологических форм [18]. В целенаправленном по-пуляционном исследовании, проанализировавшем 17 заболеваний, был продемонстрирован сложный пат-терн мультиморбидности и коморбидности в пожилом возрасте, который авторы подразделили на несколько кластеров (сосудистый, метаболический, нейродеге-неративный, ментальный в сочетании с другим кла-стером, и мышечноскелетный в сочетании с другим кла-стером) [17]. В свою очередь, хроническая комор-бидность, особенно гипертензия, сахарный диабет (СД), деменция, хроническая обструктивная болезнь лег-ких, сердечная недостаточность, ишемическая болезнь сердца, фибрилляция предсердий, рак и дисфункция щитовидной железы способствуют развитию гериат-рических синдромов (головокружение и высокий риск падений, когнитивные дисфункции, депрессия, анемия, недержание мочи, нарушения сна и др.)…”
Section: коморбидностьunclassified
“…2 This technique has been also used to characterise the complex interactions of multimorbidity and to identify the combination of biomarkers that may predict dementia. 3,4 We have also shown the use of association rules method to determine common comorbidity patterns 5 and to assess the complexity of medication use in community-dwelling older adults. 6 In our study of community-dwelling older men, we found that most interesting medication combinations differed according to geriatric syndrome status.…”
Section: Introductionmentioning
confidence: 99%